Self-compassion, adverse childhood experiences and perceived stress on college students’ mental health: The role of resilience - Hainan Li; Rong Kong; Lifang Wang (PLoS ONE, 2026)
Background The college environment presents various academic and life pressures that affect students’ mental health. Previous studies have examined self-compassion, perceived stress, and adverse childhood experiences separately, but few have integrated them within a unified resilience framework. Drawing on the stress-buffering theory, this study aims to examine the relationships among self-compassion, ACEs, perceived stress, and mental health, and to investigate the mediating role of resilience. The study develops an integrative framework that simultaneously considers risk and protective psychological mechanisms, thereby extending previous research by examining the mediating role of resilience in the associations of early adversity, stress perception, and self-compassion with mental health among university students. Methods This cross-sectional study employed an online self-report survey conducted via the Questionnaire Star platform ( www.Sojump.com ). Using a convenience sampling method, college students from two universities in China completed the Self-Compassion Scale, Adverse Childhood Experiences Scale, Perceived Stress Scale, Resilience Scale, and Mental Health Scale. A total of 657 valid questionnaires were obtained. Correlations among variables were analyzed using SPSS Statistics 26, and mediation effects were tested with Model 4 of the PROCESS 4.0 macro. Results Self-compassion was positively associated with mental health, while adverse childhood experiences and perceived stress were negatively associated with mental health. Resilience played a mediating role, linking these factors to mental health outcomes. Conclusion This study underscores the importance of resilience in mental health and provides a theoretical basis for interventions in higher education, emphasizing resilience enhancement to support student well-being.